Livius, Dionysios, Augustus, Machiavelli : ein diskursanalytischer Vergleich der römischen Frühgeschichte bei Livius und Dionysios von Halikarnassos und die Rezeption ihrer livianischen Darstellung im Werk des Niccolo Machiavelli - Haas, Philip, 1986- (Philippika, 2015)
The central part of this study is a diachronous and comprehensive analysis of the first five books of Livy and part of the sixth. Using a discourse analysis approach, the study re-evaluates the relationship between Livy and Augustus, and compares Livy's historiographical methodology with that of Dionysius of Halicarnassus. The final part of the work explores the reception of Livy's discourse in the political work of Niccolo Machiavelli.